Academic well-being and academic achievement: The role of goal orientation as a mediator - Fathiyah, Kartika Nur; Kurnia, Rahmatika; Setiyawati, Farida Agus (Insight: Jurnal Ilmiah Psikologi, 2023)
Several studies have shown the influence of academic wellbeing on academic achievement. However, some other studies do not show the same results. Researchers suspect this is due to the influence of variables that mediate the relationship between the two, namely goal orientation. Through this study, researchers examined the effect of academic wellbeing on academic achievement in students as well as examined the role of goal orientation as a mediator of the relationship between the two variables. 295 students of Universitas Negeri Yogyakarta from various study programs were involved in this research. Academic well-being was measured using the scale of academic well-being, consisting of positive affect, negative affect, and satisfaction dimensions of activities on campus. Goal orientation was measured by the goal orientation scale, consisting of mastery, performance approach, performance avoidant, and work avoidance dimensions. Academic achievement was obtained from the student cumulative achievement index (IP). The results showed that there is an influence of several dimensions of student wellbeing on goal orientation and academic achievement. In addition, this research also found that in the goal orientation variable, only the mastery dimension is predicted to play a role as a mediator of the effect of student wellbeing on academic achievement.